Hubungan Asupan Makanan dan BBLR dengan Kejadian Malnutrisi pada Balita Usia 1-5 Tahun di Wilayah Puskesmas Darul Imarah Aceh Besar - Intan Nuraini; Nunung Sri Mulyani (Jurnal Akademika Baiturrahim Jambi, 2023)
Malnutrition is an imbalance between food intake and the body's needs to fulfill specific functions of the body. Intake of macronutrients is needed by toddlers in growth and development. The imbalance in the level of consumption of macronutrients against the body's needs can affect tissue and body mass which has an impact on malnutrition. Children born with LBW have a 3.34 times greater risk of experiencing poor nutritional status compared to children who are not LBW. Objective: To determine the relationship between food intake and LBW with the incidence of malnutrition in toddlers aged 1-5 years. This research is descriptive analytic with a case control design with a total sample consisting of 31 cases and 31 controls. The research variables were food intake and LBW. This research was conducted in October 2021 at the Darul Imarah Health Center. Data analysis used Chi square test with 95% confidence level. In the case group, toddlers had adequate energy intake, mostly 22 people (44.9%), adequate carbohydrate intake 23 people (51.1%), adequate protein intake 27 people (47.4%), and fat intake deficit 31 people. (56.4%). The incidence of malnutrition in the case group was mostly experienced by 17 LBW infants (53.1%). There was a relationship between fat intake and the incidence of malnutrition (p < 0.05), while the intake of energy, carbohydrates, protein and low birth weight had no relationship with the incidence of malnutrition (p > 0.05).